1997
DOI: 10.1136/pgmj.73.864.653
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen for retroperitoneal fibrosis

Abstract: Summary Retroperitoneal fibrosis, either idiopathic or associated with aortic inflammatory aneurysm, is a chronic fibrotic disease that causes progressive obstruction of ureters and vessels around the lower abdominal aorta. Treatment is often difficult (surgery) or hazardous (steroids). We report a case of a woman with retroperitoneal fibrosis associated with aortic inflammatory aneurysm, who was successfully treated with oral tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Tamoxifen has been effective in retroperitoneal fibrosis [12,[25][26][27]. Its mechanism of action is unknown, but it has been suggested that it may exert an anti-fibrotic action through the reduction of TGF-b expression [28,29] There are anecdotal reports of the beneficial effect of tamoxifen on EPS and many of these describe its use combined with glucocorticoids [30].…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen has been effective in retroperitoneal fibrosis [12,[25][26][27]. Its mechanism of action is unknown, but it has been suggested that it may exert an anti-fibrotic action through the reduction of TGF-b expression [28,29] There are anecdotal reports of the beneficial effect of tamoxifen on EPS and many of these describe its use combined with glucocorticoids [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has, however, been widely reported as successful in the treatment of retroperitoneal fibrosis [36][37][38], but how well this translates to EPS is unclear. A recent report of its 'prophylactic' use in 9 cases of peritoneal sclerosis showed that none developed EPS, while in the control group of 14 patients with sclerosis 4 developed the syndrome and 3 died [39].…”
Section: Discussionmentioning
confidence: 99%
“…Steroids are first line therapy if there is no evidence of any mass effect such as compression of surrounding structure, vascular extension into the surrounding veins and arteries, tubular compression like ureters or organ function compromise. Steroid resistant disease can be treated by other immunosuppressive agents including cyclophosphamide, methotrexate, mycophemolate mofetil [21] colchicine [22] and tamoxifen [23].…”
Section: Discussionmentioning
confidence: 99%